Occurrence of Escherichia Coli in Packaged Drinking Water Distributed in Katabi Sub County Uganda. A Cross Sectional Study. - Byonanebye, Marion; Kizza , Emmanuel; Serunjogi, David (Student’s Journal of Health Research Africa, 2021)
Background: The world health organization (WHO) estimates that about a 1.1billion people drink unsafe water globally, and over 1.7 million deaths occur annually due to the consumption of water that is of faecal origin. Water in sachets is readily available and affordable but there is no concern about its safety. The purpose of this study was to assess the occurrence of Escherichia coli in packaged drinking water distributed in the Katabi sub country using the membrane filtration technique, isolation of organisms, and subjecting them to biochemical tests. The study was conducted in 2017. Methodology: A cross-sectional study design was used where Rwenzori, Riham water, Nevana, Highland, Blue wave, and sachet water were purposively selected in the main trading center within the Wakiso district. A total of 5 bottled water and 10 sachets of water were used. Duplicate sample (2) bottles of water from each were used. Therefore 30 samples of packaged water were used in this study. The bacteria were grown on media and confirmed using biochemical tests. Results: Sachet water contained pink lactose fermenting colonies on MacConkey culture media. Bottled water had no growth. The pink colonies were positive with Kligler iron agar (KIA), triple sugar iron agar (TSI), and sulphur and indole motility (SIM) positive. Conclusion and recommendation The majority of sachet water was contaminated with Escherichia coli an indicator of faecal contamination; and therefore, unsuitable for human consumption. The government of Uganda should carry out surveillance activities to enforce strict hygienic measures on sachet water producers and distributors.